Bahasa Inggris - Baiq Meiranti Eka Putri; Baharuddin Baharuddin; Santi Farmasari (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2023)
This article is aimed at determining the accuracy of post-editing translations on GNMT by English Department students. The objects of this study were students of the English Education Study Program, Faculty of Teacher Training and Education, University of Mataram, who were admitted to the "Translation and Interpreting" course in the fourth semester of the 2021-2022 academic year. Data obtained through observation and documentation was used in two literary texts. The results of this study indicate that almost all students have poor accuracy in their post-editing results. Most of the post-editing accuracy levels of the two texts produced by students were not acceptable, with the criteria of “highly accurate” at 1%, followed by 14% for "accurate," 35% for “less accurate,” and “inaccurate” at 51%. Based on these percentages, it can be concluded that the level of accuracy of the translation in post-editing from GNMT shows inaccurate results. Therefore, it still needs to be improved to meet the target audience by paying attention to the naturalness of the target language in terms of sentence structure, grammar, and punctuation in order to produce a better translation.